Politeness Strategies and Social Context in The Princess Switch: A Pragmatic Study - Islami, Adila Permata (Universitas Sebelas Maret, 2000)
Social interaction also requires good communication between the speaker and the listener. In everyday life, communication can lead to misunderstandings if the speaker and listener are unable to maintain a good and polite attitude. This phenomenon doses not only occur in everyday life but also in narrative forms. In building good communication, politeness is one of the crucial elements. This study discusses politeness strategies found in The Princess Switch movie using Brown and Levinson's theory. This study is a qualitative descriptive study based on four stages of analysis, namely domain analysis, componential analysis, taxonomy analysis, and cultural theme analysis. This study uses a pragmatic approach. This study identifies the use of politeness strategies, namely bald on record, positive politeness, negative politeness, and off record. Additionally, the use of politeness strategies is also based on social context, namely power and social distance. Based on the politeness strategies used in accordance with the social context in the film, the characters are formed